The trend of the gold prices in Malaysia / Mohamed Azman Mat Junoh - Mat Junoh, Mohamed Azman (2013)
Gold is a precious yellow commodity once used as money. The demand for this commodity is on the rise. The objective of this study was to know about the trend of gold prices for the past 5 years based on economic factors such as inflation, currency price movements and others. Following the melt-down of US dollars, investors are putting their money into gold because gold plays an important role as a stabilizing influence for investment portfolios. Due to the increase in demand for gold in Malaysian and other parts of the world, it is necessary to develop a model that reflects the structure and pattern of gold market and see the movement of gold price. The most appropriate approach to the understanding of gold prices is the Multiple Linear Regression (MLR) model. MLR is a study on the relationship between a single dependent variable and one or more independent variables, as this case with gold price as the single dependent variable. The fitted model of MLR will be used to predict the future gold prices.Many factors determine the price of gold and based on “a hunch of experts”, several economic factors had been identified to have influence on the gold prices. Variables such as MYR/USD Foreign Exchange Rate, Inflation rate, Money Supply (M1), Kuala Lumpur Composite Index (KLCI), and Treasury Bill (T-BILL) were considered to have influence on the prices. Parameter estimations for the MLR were carried out using Statistical Packages for Social Science package (SPSS). Only three variables that will effect the gold in this study which is foreign exchange, KLCI, and M1. The final model of this study is very important for researcher to predict the future price of gold